If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -1t = 40 Solving -16 + -1t = 40 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -1t = 40 + 16 Combine like terms: -16 + 16 = 0 0 + -1t = 40 + 16 -1t = 40 + 16 Combine like terms: 40 + 16 = 56 -1t = 56 Divide each side by '-1'. t = -56 Simplifying t = -56
| 211+z=657 | | b-93=-12 | | 12.4d=111.6 | | c+3/10=31/70 | | 0.6(5s-6)=2.4 | | 12x+2=39 | | 2u^3-5u^2-6u=-15 | | 9u-15=7u-5 | | n-0.41=.09 | | a-733=129 | | 85=100-x | | 2u^3-5u^2-64=-15 | | 1.2(t+2.3)=3.96 | | 6y-8y=2 | | 3-1/4x=3/2 | | -6/25=-4/5p | | 7(x+3)-7=22-3x-8+10x | | 85=1-x | | 0.02=0.8(y+0.1) | | -7c=41/5 | | 1/5X+2=15 | | -6+8(x-2)=15x+6-7x | | 9+7y=-21 | | 2(x-3)+5x=5+7(x+3) | | 1=-8+2x | | -9=2v-3 | | 6x-(2x-3)=4x+5 | | x^4+4x^3+12x^2+12x-9=0 | | X/3+6=11 | | -5s=-1.25 | | 13x+19y=-17 | | 6x+75=9x+93 |